Differentiation of Multivalued Mappings. T-Derivative - Plotnikov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider several approaches to the differentiation of multivalued mappings and introduce a new definition of derivative (T-derivative), which generalizes the Hukuhara derivative.